Mechanism of peroxidase-mediated oxidation of carcinogenic o-anisidine and its binding to DNA - Stiborová, Marie; Miksanová, Markéta; Havlícek, Vladimír; Schmeiser, Heinz H; Frei, Eva (Mutation research, 2002)
2-Methoxyaniline (o-anisidine) is a urinary bladder carcinogen in both mice and rats. Since the urinary bladder contains substantial peroxidase activity, we investigated the metabolism of this carcinogen by prostaglandin H synthase (PHS), a prominent enzyme in the urinary bladder, and lactoperoxidase as model mammalian peroxidases. Horseradish peroxidase (HRP)-mediated oxidation of o-anisidine was also determined and compared with the reactions catalyzed by mammalian peroxidases. All three peroxidases oxidized o-anisidine via a radical mechanism. Using HPLC combined with electrospray tandem mass spectrometry, we determined that peroxidases oxidized o-anisidine to a diimine metabolite, which subsequently hydrolyzed to form a quinone imine. Two additional metabolites were identified as a dimer linked by an azo bond and another metabolite consisting of three methoxybenzene rings, which exact structure has not been identified as yet. Using [14C]-labeled o-anisidine, we observed substantial peroxidase-dependent covalent binding of o-anisidine to DNA, tRNA and polydeoxynucleotides [poly(dX)]. The 32P-postlabeling assay (a standard procedure and enrichment of adducts by digestion with nuclease P1 or by extraction into 1-butanol prior to 32P-labeling) was employed as the second method to detect and quantitate binding of o-anisidine to DNA. Using these versions of the 32P-postlabeling technique we did not observe any DNA adducts derived from o-anisidine. The o-anisidine-DNA adducts became detectable only when DNA modified by o-anisidine was digested using three times higher concentrations of micrococcal nuclease and spleen phosphodiesterase (MN/SPD). We found deoxyguanosine to be the target for o-anisidine binding in DNA using poly(dX) and deoxyguanosine 3'-monophosphate (dGp). A diimine metabolite of o-anisidine is the reactive species forming adducts in dGp. The results strongly indicate that peroxidases play an important role in o-anisidine metabolism to reactive species, which might be responsible for its genotoxicity, and its carcinogenicity to the urinary bladder in rodents. The limitation of the 32P-postlabeling technique to analyze DNA adducts derived from o-anisidine as a means to estimate its genotoxicity is discussed.
Keywords: karcinogeny; Lactoperoxidase; Rats; Seminal Vesicles; NAD; ovce; nádory močového měchýře; DNA; mikrozomy; Glutathione; semenné váčky; mužské pohlaví; Mice; Oxidation-Reduction; křenová peroxidasa; aniliny; Microsomes; krysa rodu Rattus; zvířata; Aniline Compounds; glutathion; laktoperoxidasa; Binding Sites; Carcinogens; Horseradish Peroxidase; myši; Urinary Bladder Neoplasms; oxidace-redukce; Sheep; hmotnostní spektrometrie s elektrosprejovou ionizací; Indomethacin; indomethacin; vazebná místa; Spectrometry, Mass, Electrospray Ionization; Male; Animals